PP-046 A stability indicating hplc-uv method for quantification of simvastatin and detection of its impurities in oral capsules. (25th February 2017) - Merienne, C; Semely, D; Wolff, E; Roussiere, A; Tafani, M; Ramjaun, Z; Caturla, L
Abstract : Background: A clinical trial sponsored by our hospital wished to compare HMG-CoA reductase inhibitors versus placebo for children with genetic diseases. For this purpose, and because the dosage in unavailable, our laboratory is in charge of the galenic development of simvastatin capsules and its placebo. According to GMP, the stability of the simvastatin capsule is evaluated. Purpose: Development and validation of a stability indicating HPLC-UV method for simvastatin capsules. Material and methods: The HPLC system is a Thermofisher P4000. The column is an inertsil-CN, 250×4.6 mm with 5 µm particle. The mobile phase is an isocratic elution made up of 0.1% acetic acid buffer/methanol (50:50 v/v) at 1 mL/min flow rate. λ is included between 200 and 400 nm. Maximal absorbance of simvastatin is 237 nm. Calibration standard curve is between 30 and 70 µg/mL. Niacin is used as the internal standard. Linearity, trueness, accuracy and limits of quantification were evaluated according to SFSTP recommendations. Impurities were searched from SCR impurities of simvastatin dust according to pharmacopoeia 8.0. The matrix effect was evaluated. Results: Linearity for simvastatin was validated with r² >0.99 and SD <15%. Recoveries and bias were < 15% for each validation standard. High and low limits of detections were far from the calibration standard curves. There was no matrix effect with the excipients. All impurities were detected and separated with a resolution >1.5. Conclusion: A simple and rapid stability indicating HPLC-UV method was developed and validated according to ICH and SFSTP international recommendations. It will be used to evaluate the stability of our simvastatin capsule. We already have 3 months of validated stability. No conflict of interest